PROFIL FITOKIMIA DAN PENGARUH EKSTRAK TANGKAI DAUN TALAS KEMUMU (Colocasia gigantea Hook.f ) TERHADAP JUMLAH LEUKOSIT Mus musculus - Rofiqa Asri; Dewi Handayani; Agus Sundaryono (ALOTROP, 2019)
This research aims to identify secondary metabolite compounds in Talas kemumu leaf stalk (Colocasia gigantea Hook.f) and to determine the effect of extract on the number of male Mus musculus leukocytes that have been induced aspirin. Aspirin is used to increase the number of M.musculus leucocytes.The method used in this research is the method of extraction by maceration to attract secondary metabolites of active compounds  C.gigantea leaf stalk and the measurement of blood leukocyte counts are calculated using a hemocytometer (improved neubauer). Test of the effect of the leaf stalk of C.giganteaextract on the number leukocytes of M.musculus  was performed by dividing into 5 groups with 5 replications according to the Federer formula, namely K (-) were given distilled water, K (+) were given aspirin, P1, P2 and P3 are each given a dose of extract of  C.gigantea leaf stalk of 0,028 g/KgBB, 0,056 g/KgBB and 0,084 g/KgBB. The results showed that the identification of phytochemical profile in C.gigantea leaf stalk contains secondary metabolite compounds such as alkaloids, flavonoids, terpenoids, tannins and saponins. The results shows that giving of C.gigantea leaf stalk extract can reduce the number of leukocytes M.musculus which have induced aspirin. The giving of C.gigantea leaf stalk extract can decrease the number of aspirin-induced M.musculus leukocytes. This is evident from the results of One Way Anova analysis and the Smallest Real Difference Test (BNT) because in each treatment group has a significant influence. The effective dose that has the greatest activity in decreasing the number of M.musculus leukocytes found in the P1 treatment of 0,028 g /KgBB can decrease the blood leukocyte count by 6,830 / mm3.